2015
DOI: 10.1002/hbm.22986
|View full text |Cite
|
Sign up to set email alerts
|

Developmental evaluation of atypical auditory sampling in dyslexia: Functional and structural evidence

Abstract: Whether phonological deficits in developmental dyslexia are associated with impaired neural sampling of auditory information at either syllabic- or phonemic-rates is still under debate. In addition, whereas neuroanatomical alterations in auditory regions have been documented in dyslexic readers, whether and how these structural anomalies are linked to auditory sampling and reading deficits remains poorly understood. In this study, we measured auditory neural synchronization at different frequencies correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
85
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 92 publications
12
85
2
3
Order By: Relevance
“…Because this component of speech is typically processed at low frequencies in the right auditory cortex and is thought to result from poorer or impaired oscillatory synchronization between theta oscillations (syllable rate) and delta (stress rate) oscillations, we expect to find reduced synchronization in the delta range within this area in children at 15 risk for dyslexia. We also anticipate to observe atypical synchronization in the theta band in these children, which is expected to be stronger in children speaking syllable-timed languages as Spanish, as previously observed by Lizarazu et al (2015), because stress-timed languages like English typically contain more complex and varied syllabic onsets and codas (Dauer, 1983;Auer, 1991), as well as shorter unstressed vowels (Ramus, Nespor & Mehler, 1999).…”
Section: Brain Rhythms As Biomarkers Of Dyslexiasupporting
confidence: 60%
See 1 more Smart Citation
“…Because this component of speech is typically processed at low frequencies in the right auditory cortex and is thought to result from poorer or impaired oscillatory synchronization between theta oscillations (syllable rate) and delta (stress rate) oscillations, we expect to find reduced synchronization in the delta range within this area in children at 15 risk for dyslexia. We also anticipate to observe atypical synchronization in the theta band in these children, which is expected to be stronger in children speaking syllable-timed languages as Spanish, as previously observed by Lizarazu et al (2015), because stress-timed languages like English typically contain more complex and varied syllabic onsets and codas (Dauer, 1983;Auer, 1991), as well as shorter unstressed vowels (Ramus, Nespor & Mehler, 1999).…”
Section: Brain Rhythms As Biomarkers Of Dyslexiasupporting
confidence: 60%
“…For instance, differences in low frequency temporal features, like the theta band at 4 Hz, seem to exist between dyslexic children using syllable-timed rhythmic languages like Spanish and children using stress-timed languages like English. Accordingly, Spanish children with dyslexia show stronger synchronization of theta at 4 Hz in the auditory cortex (Lizarazu et al, 2015) compared to English dyslexics (Lehongre, Morillon, Giraud, & Ramus, 2013). This suggests that dyslexics using syllabletimed languages rely to a greater extent on phonemic information to compensate for an impaired right specialization of the gamma band.…”
Section: Why Brain Rhythmsmentioning
confidence: 96%
“…For example, we expect larger phonological-grain-size strategies to result in a greater number of deletion errors such as first-syllable or onset deletions (i.e., /platu/ being segmented as /pla//tu/ or /pl//atu/ instead of /p// latu/). At the brain level, a stronger bias toward left auditory cortex may be found in response to phonological items among individuals highly sensitive to phonemic details than among individuals who rely more on larger phonological units such as syllables (Lizarazu et al, 2015;Molinaro, Lizarazu, Lallier, Bourguignon, & Carreiras, 2016;Poeppel, 2003).…”
Section: Predictions Of the Grain Size Accommodation Hypothesismentioning
confidence: 99%
“…Recent studies with adults and children with developmental dyslexia have consistently reported atypical neural activity related to auditory processing (Abrams et al, 2009, Lehongre et al, 2011, Poelmans et al, 2012, Hornickel and Kraus, 2013, Power et al, 2013, Lizarazu et al, 2015). However, none of these recent auditory studies has used a reading level (RL) match control group, an important research design for helping to distinguish cause from effect in studies of developmental disorders (Goswami, 2003).…”
Section: Introductionmentioning
confidence: 99%